THE ROLE OF THE INTEGRATIVE CURRICULUM IN STUDENT CHARACTER DEVELOPMENT IN MTS - Dullah, Bayu Saputra; Abdullah, Asni (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study aims to examine the role of an integrative curriculum in character development among students at Madrasah Tsanawiyah (MTs) through a literature review using a descriptive narrative approach. The analysis reveals that the integrative curriculum at MTs combines general subjects with Islamic values, including general subjects taught from an Islamic perspective, religious subjects, and extracurricular activities based on spiritual values. This curriculum has been shown to positively impact students' character development, including improvements in morality and ethics, social competence, and a balance between academic knowledge and understanding of religious values. However, implementing the integrative curriculum faces challenges, such as limited resources and difficulties in integrating general subject matter with spiritual values. Government policies and innovations in teaching methods and educational technology support opportunities for curriculum development. This study provides significant insights into the role of the integrative curriculum at MTs and highlights the importance of continuous support from the government and academic institutions. The study also recommends further empirical research to obtain direct data from students, teachers, and school principals and explore technology's use in supporting the integrative curriculum.